The PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS WEBSITE PADA EKSTRAKURIKULER TEKNOLOGI INFORMASI DAN KOMUNIKASI DI SMP MUHAMMADIYAH TANJUNG SELOR - Sahid Setiawan Aci; Iis Siti Aisyah; Lud Waluyo (Educational Technology Journal, 2025)
This research aimed to develop a valid, practical, and effective website-based learning media to support Information and Communication Technology extracurricular activities at SMP Muhammadiyah Tanjung Selor. The study employed Research and Development methodology using the ADDIE model (Analyze, Design, Development, Implementation, Evaluation) with purposive sampling technique involving 25 students participating in ICT extracurricular activities. Data collection was conducted through questionnaires, observations, interviews, and literature studies, while data analysis utilized descriptive qualitative and statistical descriptive techniques. The research results demonstrated that the developed website-based learning media achieved material expert validation score of 77% (Good category) and media expert validation score of 80% (Very Good category), indicating valid criteria. Student responses during implementation showed positive feedback with average percentages of 92.7% for the first meeting, 81.6% for the second meeting, and 85.3% for the third meeting, all categorized as Very Good. Teacher responses reached 90% (Very Good category), confirming the media's practicality. Effectiveness was proven through significant improvement in pre-test and post-test results, showing enhanced student understanding of ICT concepts, hardware-software identification, word processing applications, and digital design using Canva.